Myocardial Injury and the Risk of Stroke in Patients With Chronic Kidney Disease (From the Chronic Renal Insufficiency Cohort Study). (April 2022) - Hajjari, Jamal; Janus, Scott E.; Albar, Zainab; Al-Kindi, Sadeer G.
Patients with chronic kidney disease (CKD) are at increased risk for stroke. High-sensitivity troponin (hsTP), a marker of myocardial injury, has been associated with stroke risk in patients without CKD, but whether this applies to patients with CKD is not known. We assessed whether hsTP levels is associated with incident stroke in patients with mild-to-moderate CKD without a history of stroke enrolled in the Chronic Renal Insufficiency Cohort. Patients were followed for incident stroke, and the association with hsTP was assessed. A total of 3477 patients without prior stroke were included in this investigation. Over a median follow-up of 7.3 years, 101 (2.8%) patients had an incident stroke. Baseline hsTP was associated with a 9-year risk of stroke (quartile 1: 1.8%, quartile 2: 3.8%, quartile 3: 4.9%, quartile 4: 7.3%; P < .001). After adjusting for traditional stroke risk factors, patients in the fourth quartile (hazard ratio: 2.52, 95% CI: 1.10-5.76, P = .021) had higher risk of stroke when compared with the lowest quartile of hsTP. In conclusion, hsTP levels are associated with increased risk of incident stroke in patients with mild to moderate CKD, and this association remains significant despite the adjustment for traditional risk factors and CKD.